Parental involvement in the war in Croatia 1991-1995 and suicidality in Croatian male adolescents - Franić, Tomislav (Croatian Medical Schools, 2012)
AIM: To investigate the association between parental war involvement and different indicators of psychosocial distress in a community sample of early adolescents ten years after the war in Croatia 1991-1995. METHODS: A total of 695 adolescents were screened with a self-report questionnaire assessing parental war involvement, sociodemographic characteristics, and alcohol and drug consumption. Personality traits were assessed with the Junior Eysenck Personality Questionnaire; depressive symptoms with the Children’s Depression Inventory (CDI); and unintentional injuries, physical fighting, and bullying with the World Health Organization survey Health Behavior in School-aged Children. Suicidal ideation was assessed with three dichotomous items. Suicidal attempts were assessed with one dichotomous item. RESULTS: Out of 348 boys and 347 girls who were included in the analysis, 57.7% had at least one veteran parent. Male children of war veterans had higher rates of unintentional injuries (odds ratio [OR], 1.2; 95% confidence interval [CI], 0.56 to 2.63) and more frequent affirmative responses across the full suicidal spectrum (thoughts about death – OR, 2.1; 95% CI, 1.02 to 4.3; thoughts about suicide – OR, 5; 95% CI, 1.72 to 14.66; suicide attempts – OR, 3.6; 95% CI, 1.03 to 12.67). In boys, thoughts about suicide and unintentional injuries were associated with parental war involvement even after logistic regression. However, girls were less likely to be affected by parental war involvement, and only exhibited signs of psychopathology on the CDI total score. CONCLUSION: Parental war involvement was associated with negative psychosocial sequels for male children. This relationship is possibly mediated by some kind of identification or secondary traumatization. Suicidality and unintentional injuries are nonspecific markers for a broad range of psychosocial distresses, which is why the suggested target group for preventive interventions should be veteran parents as vectors of this distress.